Detection of Multidrug-Resistant Klebsiella pneumoniae in Intensive Care Units - Muhammad Ahsan Razza; Arebaa Kholid; Syeed Hamza Naqvi (Magenta Journal De Healthymedi, 2026)
This study investigates the detection of multidrug-resistant (MDR) Klebsiella pneumoniae among Intensive Care Unit patients in tertiary healthcare hospitals in Pakistan. The research aims to identify the prevalence, resistance patterns, and clinical factors associated with MDR Klebsiella pneumoniae infections in ICU settings. A quantitative cross-sectional design was employed using microbiological culture and antimicrobial susceptibility testing based on Clinical and Laboratory Standards Institute guidelines. Clinical specimens, including tracheal aspirates, blood, urine, sputum, and wound swabs, were collected from ICU patients with suspected bacterial infections. The findings revealed a high prevalence of MDR Klebsiella pneumoniae, with substantial resistance against third-generation cephalosporins, fluoroquinolones, aminoglycosides, and carbapenems. Prolonged ICU hospitalization, mechanical ventilation, urinary catheter use, and prior antibiotic exposure were significantly associated with MDR occurrence. The study contributes to antimicrobial resistance literature by providing updated epidemiological evidence and practical implications for strengthening infection control strategies, antimicrobial stewardship programs, and hospital surveillance systems in developing healthcare settings.